Comparative researches of wearproofness of standards are with different properties in a model abrasive environment - Гончар, В.А. (Problems of Tribology, 2014)
The results of comparative experimental studies of wear resistance of steel samples with different chemical and heat treatment in a medium abrasive solution model that simulates the conditions of the extruder during processing feed grains.